Утворення та діяльність архівів президента в пострадянських країнах - Надольська, Валентина; Nadolska, Valentyna (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті висвітлено історію формування президентських архівів у пострадянських країнах. Розкрито нормативно-правові засади їхнього функціонування, завдання, функції, склад фондів, місце в системі архівних установ незалежних держав. Схарактеризовано основні напрями діяльності архівів президента у Російській Федерації, Республіці Казахстан, Киргизькій Республіці.The article highlights the history of formation of the Archives of the President in the post-Soviet countries, particularly in the Russian Federation, the Republic of Kazakhstan, the Kyrgyz Republic, the Republic of Turkmenistan. The introduction of the institution's presidency after the proclamation of independence was the main determinant of their formation. The Archives of the President are implementing the permanent state safekeeping and use of documents generated by the activities of the president and his administration.
The Formation and Activities of the Archives of the President in the Post-Soviet Countries
Keywords: архів президента; Російська Федерація; Республіка Казахстан; Киргизька Республіка; Республіка Туркменістан; пострадянські країни; the Archive of the President; the Russian Federation; the Republic of Kazakhstan; the Kyrgyz Republic; the Republic of Turkmenistan; the post-Soviet countries